Integritas Sistem Pembayaran Digital (QRIS) Bagi Pelaku UMKM - Husna, Asmaul; Arsyad, Andi Asy'hary J.; Permata, Reny Amalia; Insani, Chairi Nur; Mala, Faiqotul (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2024)
To ensure that micro, small, and medium-sized enterprises (MSMEs) in Indonesia implement the Digital Payment System Integrity (QRIS), effective monitoring efforts involving social responsibility are required. The purpose of this dedication to the community is to find out how UMKM perpetrators understand QRIS integration and the problems they face. The implementation methods used include direct support, surveys, transaction monitoring, practical training, and understanding of QRIS and digital payment systems. Therefore, Commitment to the Society provides guidelines for implementing commitment initiatives in the community that focus on QRIS integration for small and medium-sized enterprises. (UMKM). In addition, this PkM will help to expand financial inclusion and inclusive economic growth in Indonesia.